Immediate and long-term results of the treatment of patients with rectal cancer - O. I. Kit; Yu. A. Gevorkyan; N. V. Soldatkina; V. E. Kolesnikov; O. K. Bondarenko; E. K. Khabzhokov; R. E. Tolmakh; A. V. Dashkov; D. S. Petrov; D. A. Savchenko; E. N. Kolesnikov; A. V. Snezhko (Сибирский онкологический журнал, 2023)
The purpose of the study was to analyze rectal resection outcomes in patients with rectal cancer.Material and Methods. A retrospective analysis of treatment outcomes of 251 patients with stage cT3–4aN0–2M0 rectal cancer, who underwent transperitoneal resections of the rectum with mesorectumectomy from 2015 to 2020, was carried out. The age of the patients ranged from 27 to 90 years. Considering the extent of rectal tumor spread, 143 (56.9 %) patients underwent neoadjuvant prolonged conformal radiation therapy or chemoradiotherapy.Results. The failure of the colorectal anastomosis was observed in 11 (4.4 %) patients, repeated surgery was performed in 8 (72.7 %) patients (Grade C). During the follow-up, disease progression was detected in 58 (23.1 %) patients, tumor recurrence in the rectum occurred in 2 (0.8 %) patients, and distant metastases were found in 56 (22.3 %) patients. Statistical analysis showed that the parameters, such as the age, localization of the tumor in the rectum, tumor grade and T stage did not significantly affect the disease progression. A statistically significant relationship between the disease progression and pN2 stage was revealed. Patients with pN2 stage were 4.1 times more likely to have disease progression. The 75th percentile survival time was51.2 months. Patients with pN2 stage had a 3.6-fold increase in the risk of lethal outcome.Conclusion. The study demonstrated good oncological and surgical outcomes in the treatment of stage II–III rectal cancer with high survival rates. Resection of the rectum in patients with rectal cancer is a safe and predictable surgical procedure accompanied by a low incidence of anastomotic leaks and disease recurrence. The pN2 stage in rectal cancer patients significantly worsened the oncologic outcomes and survival of patients.